Molecular elucidation of drug-induced abnormal assemblies of the hepatitis B virus capsid protein by solid-state NMR - Lauriane Lecoq; Louis Brigandat; Rebecca Huber; Marie-Laure Fogeron; Shishan Wang; Marie Dujardin; Mathilde Briday; Thomas Wiegand; Morgane Callon; Alexander Malär; David Durantel; Dara Burdette; et al. (Nature Communications, 2023)
Hepatitis B virus (HBV) capsid assembly modulators (CAM) represent a recent class of anti-HBV antivirals. Structural approaches provide limited conformational information on the CAM-induced off-path assemblies. Here, authors use solid-state NMR to establish a structural view on assembly modulation of the HBV capsid.